Febrile seizures: a population-based study - Juliane S. Dalbem; Heloise H. Siqueira; Mariano M. Espinosa; Regina P. Alvarenga (Elsevier, 2015)
Objectives: To determine the prevalence of benign febrile seizures of childhood and describe the clinical and epidemiological profile of this population. Methods: This was a population-based, cross-sectional study, carried out in the city of Barra do Bugres, MT, Brazil, from August 2012 to August 2013. Data were collected in two phases. In the first phase, a questionnaire that was previously validated in another Brazilian study was used to identify suspected cases of seizures. In the second phase, a neurological evaluation was performed to confirm diagnosis. Results: The prevalence was 6.4/1000 inhabitants (95% CI: 3.8-10.1). There was no difference between genders. Simple febrile seizures were found in 88.8% of cases. A family history of febrile seizures in first-degree relatives and history of epilepsy was present in 33.3% and 11.1% of patients, respectively. Conclusions: The prevalence of febrile seizures in Midwestern Brazil was lower than that found in other Brazilian regions, probably due to the inclusion only of febrile seizures with motor manifestations and differences in socioeconomic factors among the evaluated areas. Resumo: Objetivos: Estabelecer a prevalência das crises febris e descrever o perfil clínico e epidemiológico dessa população. Métodos: Estudo transversal de base populacional realizado na cidade de Barra do Bugres (MT), no período de agosto de 2012 a agosto de 2013. Os dados foram coletados em duas etapas. Na primeira fase utilizamos um questionário validado previamente em outro estudo brasileiro, para identificação de casos suspeitos de crises epilépticas. Na segunda etapa realizamos a avaliação neuroclínica para confirmação diagnóstica. Resultados: A prevalência de crise febril foi de 6,4/1000 habitantes (IC95% 3,8; 10,1). Não houve diferença entre os sexos. As crises febris simples foram encontradas em 88,8% dos casos. A história familiar de crise febril e epilepsia em parentes de 1° grau esteve presente em 33,3% e 11,1% dos pacientes, respectivamente. Conclusões: A prevalência da crise febril na região centro-oeste foi menor do que a encontrada em outras regiões brasileiras, provavelmente relacionado à inclusão apenas das crises febris com manifestações motoras e as diferenças de fatores socioeconômicos entre as regiões pesquisadas. Keywords: Prevalence, Febrile seizure, Epidemiology, Palavras-chave: Prevalência, Crise febril, Epidemiologia